2021
DOI: 10.1016/j.xjidi.2021.100039
|View full text |Cite
|
Sign up to set email alerts
|

Seeing through the Skin: Photoacoustic Tomography of Skin Vasculature and Beyond

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 166 publications
(204 reference statements)
0
43
0
Order By: Relevance
“…[ 81 ] OAM can cover all layers composing the human skin and has been shown to represent a valuable tool to visualize psoriasis and eczema [ 13 ] or burns and other wounds. [ 82 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 81 ] OAM can cover all layers composing the human skin and has been shown to represent a valuable tool to visualize psoriasis and eczema [ 13 ] or burns and other wounds. [ 82 ]…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a salivary gland stimulation challenge conducted in mouse models, a decrease in sO 2 change between measurements taken before and after salivary stimulation post-EBRT was associated with radiation-induced salivary gland toxicity in a murine model assessed with macroscopic PAI ( Figure 1B ) ( 60 ). Mesoscopic implementations of PAI can achieve ~20 μm in-plane resolution up to ~3 mm in depth for skin imaging ( 52 , 127 ), indicating potential for clinical skin toxicity assessment ( 128 ). Preliminary work on skin atopic dermatitis grading ( 61 ) showed that combining PAI mesoscopy-derived total blood volume, average vessel diameter, and ratio of low to high frequency signals gave a discriminating signature for atopic skin dermatitis grade ( Figure 1C ) ( 129 ).…”
Section: Potential Uses Of Photoacoustic Imaging In Radiotherapymentioning
confidence: 99%
“…With the introduction of exogenous contrast agents, it is also possible to directly report on tumor tissue pO 2 ( 51 ). Moreover, PAI is scalable for non-invasive assessment of single capillaries and even red blood cells ( 52 ) and can also be used to extract information on blood flow ( 53 ). PAI has thus been proposed for application in superficial tumors to improve: radiation dose delivery and scheduling; patient stratification; and therapy response and radiation side effects monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Although most melanomas are pigmented, around 5–10% of cutaneous melanomas are amelanotic, which may cause delayed detection and worse prognosis ( Chen and Sebaratnam, 2021 ; Chuchvara et al, 2021 ). From dermoscopy through reflectance confocal microscopy (RCM) to histology, this condition emphasizes difficulties in the diagnosis of amelanotic melanoma ( Li et al, 2021 ; Rasmussen et al, 2021 ; Williams et al, 2021 ).…”
Section: Dilemma Of Skin Cancer Theranosticsmentioning
confidence: 99%